2018
DOI: 10.3390/bdcc2030020
|View full text |Cite
|
Sign up to set email alerts
|

A User Study of a Prototype of a Spatial Augmented Reality System for Education and Interaction with Geographic Data

Abstract: Recent technological advancements in many areas have changed the way that individuals interact with the world. Some daily tasks require visualization skills, especially when in a map-reading context. Augmented Reality systems could provide substantial improvement to geovisualization once it enhances a real scene with virtual information. However, relatively little research has worked on assessing the effective contribution of such systems during map reading. So, this research aims to provide a first look into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…Subsequently, AR might guide students on how to correctly understand, analyze, and evaluate maps. In a study by Pereira et al [44], the participants validated their drawings of geographic features (e.g., rivers and potential dams) with AR. The learners reported that they felt comfortable by getting feedback from the AR system.…”
Section: Related Workmentioning
confidence: 99%
“…Subsequently, AR might guide students on how to correctly understand, analyze, and evaluate maps. In a study by Pereira et al [44], the participants validated their drawings of geographic features (e.g., rivers and potential dams) with AR. The learners reported that they felt comfortable by getting feedback from the AR system.…”
Section: Related Workmentioning
confidence: 99%